UPAYA DIPLOMASI BUDAYA KEDUTAAN BESAR REPUBLIK INDONESIA (KBRI) MOSKOW DALAM MENINGKATKAN KEMBALI WISATAWAN RUSIA DI INDONESIA PADA PERIODE TAHUN 2020-2022 - Fahreza Resta Dwiputra (2024)
The relationship between Indonesia and Russia has been established since the time of President Soekarno's administration, and over time, the relationship between the two countries has continued to develop. The outcome of this relationship has led to an increase in Russian tourists visiting Indonesia every year. Unfortunately, during the period of 2020-2022, the number of Russian tourists visiting Indonesia experienced a decline. Therefore, the role of Indonesia's representative actor in Russia, namely the Embassy of the Republic of Indonesia in Moscow, plays a crucial role in increasing Russian tourists visiting Indonesia. Cultural diplomacy is certainly a very important solution to address this issue, aiming to rekindle the interest of the Russian public in Indonesia. This research aims to determine the efforts made by the Embassy of the Republic of Indonesia in Moscow to increase Russian tourists visiting Indonesia through cultural diplomacy during the period of 2020-2022. The research method used in this study is descriptive qualitative, where the results identify the cultural diplomacy conducted by the Embassy of the Republic of Indonesia in Moscow during the period of 2020-2022.